2015
DOI: 10.1371/journal.pone.0134459
|View full text |Cite|
|
Sign up to set email alerts
|

The Effects of Compensatory Scanning Training on Mobility in Patients with Homonymous Visual Field Defects: A Randomized Controlled Trial

Abstract: IntroductionHomonymous visual field defects (HVFD) are a common consequence of postchiasmatic acquired brain injury and often lead to mobility-related difficulties. Different types of compensatory scanning training have been developed, aimed at decreasing consequences of the HVFD by changing visual scanning.AimThe aim of the present study is to examine the effects of a compensatory scanning training program using horizontal scanning on mobility-related activities and participation in daily life.MethodThe main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 47 publications
(73 reference statements)
0
56
0
Order By: Relevance
“…A number of studies have specifically reported on subjective improvements in activities of daily living following compensatory therapy, such as improvements in mobility, reading, driving, and detection of obstacles (Bergsma et al., 2011; Ong et al., 2015; Keller & Lefin‐Rank, 2010; Aimola et al., 2014; Jacquin‐Courtois et al., 2013; Kerkhoff et al., 1994; Mazer et al., 2003; de Haan, Melis‐Dankers, Brouwer, Tucha, & Heutink, 2015; Hayes, Chen, Clarke, & Thompson, 2012; Nelles et al., 2001; Rowe, Conroy, et al., 2016). A study by de Haan et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have specifically reported on subjective improvements in activities of daily living following compensatory therapy, such as improvements in mobility, reading, driving, and detection of obstacles (Bergsma et al., 2011; Ong et al., 2015; Keller & Lefin‐Rank, 2010; Aimola et al., 2014; Jacquin‐Courtois et al., 2013; Kerkhoff et al., 1994; Mazer et al., 2003; de Haan, Melis‐Dankers, Brouwer, Tucha, & Heutink, 2015; Hayes, Chen, Clarke, & Thompson, 2012; Nelles et al., 2001; Rowe, Conroy, et al., 2016). A study by de Haan et al.…”
Section: Resultsmentioning
confidence: 99%
“…A study by de Haan et al. (2015) examined the effect of compensatory scanning training on mobility‐related activities and found a link between visual scanning training and detection of peripheral stimuli and obstacle avoidance. This evidence provides further support for the role of compensatory treatment in the adaptation process.…”
Section: Resultsmentioning
confidence: 99%
“…There are neither theoretical reasons nor empirical evidence to support the idea that either visual search training or peripheral prisms would result in visual field recovery. In fact, prior studies have reported no effects of search training 8, 9, 11 or peripheral prisms 4 on visual field size (when measured without prisms). Indeed, the Rowe et al paper 1 even cited a recent Cochrane systematic review 15 of interventions for post-stroke field loss stating that the review “concluded that, generally, interventions for homonymous hemianopia do not result in improvement of visual field”.…”
Section: Dear Editormentioning
confidence: 88%
“…3, 4, 6, 7 When not worn, the prisms are not expected to provide any help or effect. Visual search training is expected to increase visual exploration (scanning) toward the blind hemifield, 810 which may in turn improve detection of objects on the blind side. 8, 11 …”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation